Efficacy of garlic (Allium sativum) extract applied as a therapeutic immersion treatment for Neobenedenia sp. management in aquaculture - T A Militz; P C Southgate; A G Carton; K S Hutson (John Wiley & Sons Ltd, 2025)
Garlic, Allium sativum L., extract administered as a therapeutic bath was shown to have antiparasitic properties towards Neobenedenia sp. (MacCallum) (Platyhelminthes: Monogenea) infecting farmed barramundi, Lates calcarifer (Bloch). The effect of garlic extract (active component allicin) immersion on Neobenedenia sp. egg development, hatching success, oncomiracidia (larvae) longevity, infection success and juvenile Neobenedenia survival was examined and compared with freshwater and formalin immersion. Garlic extract was found to significantly impede hatching success (5% 5%) and oncomiracidia longevity (<2 h) at allicin concentrations of 15.2 lL L 1, while eggs in the seawater control had >95% hatching success and mean oncomiracidia longevity of 37 3 h. At much lower allicin concentrations (0.76 and 1.52 lL L 1), garlic extract also significantly reduced Neobenedenia infection success of L. calcarifer to 25% 4% and 11% 4%, respectively, compared with 55% 7% in the seawater control. Juvenile Neobenedenia attached to host fish proved to be highly resistant to allicin with 96% surviving 1-h immersion in 10 mL L 1 (15.2 lL L 1 allicin) of garlic extract. Allicin-containing garlic extracts show potential for development as a therapy to manage monogenean infections in intensive aquaculture with the greatest impact at the egg and larval stages.